PERAN MEDIA PENYULUHAN (STUDI KASUS PADA KELOMPOK “GAWI BERSAMA DAN BAIMBAI SEJAHTERA”) DI DESA JEMBAYAN KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA: PERAN MEDIA PENYULUHAN (STUDI KASUS PADA KELOMPOK “GAWI BERSAMA DAN BAIMBAI SEJAHTERA”) DI DESA JEMBAYAN KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA - pai, vinsensiua; Haqiqiansyah, Gusti; Juliani (2339-1324, 2024)
Fishery counseling is non-formal education aimed at the community, especially fishermen, cultivators and processors of fishery products and their families to improve knowledge, skills, attitudes and motivation in the field of fisheries. The Role of Extension Media on Fish Cultivators in Jembayan Village, Kutai Kartenegara Regency, it is necessary to do counseling with extension media to see whether the use of media in the extension carried out is effective to be understood and carried out in aquaculture practices as conveyed by the fishery instructor. This study aims to identify fishery extension media used in extension activities in the